2016
DOI: 10.3906/elk-1309-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of AR parametric methods with subspace-based methods for EMG signal classification using stand-alone and merged neural network models

Abstract: Abstract:This research introduces an electromyogram (EMG) pattern classification of individual motor unit action potentials (MUPs) from intramuscular electromyographic signals. The presented technique automatically classifies EMG patterns into healthy, myopathic, or neurogenic categories. To extract a feature vector from the EMG signal, we use different autoregressive (AR) parametric methods and subspace-based methods. The proposal was validated using EMG recordings composed of 1200 EMG patterns obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
(63 reference statements)
0
9
0
1
Order By: Relevance
“…Finally, in [10], the classification accuracy improved to 97.67% due to the use of DWT method for feature extraction and evolutionary SVM for classification. Furthermore, after several years, Bozkurt et al [13] suggested a model for classifying EMG signal through the use of MUSIC method for feature extraction, combined neural network for classification, and the same dataset. This model was proposed in 2016 and it achieved 94% accuracy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in [10], the classification accuracy improved to 97.67% due to the use of DWT method for feature extraction and evolutionary SVM for classification. Furthermore, after several years, Bozkurt et al [13] suggested a model for classifying EMG signal through the use of MUSIC method for feature extraction, combined neural network for classification, and the same dataset. This model was proposed in 2016 and it achieved 94% accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Bozkurt et al [13] employed several parametric methods and subspace-based methods for EMG recordings composed of normal, neurogenic, and myopathic subjects. A combined neural network (CNN) and FEBANN were employed for classification, and the highest performance was achieved with the eigenvector method.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors used autoregressive models and the characteristics of random processes, such as first and second moments, etc., in tasks related to the classification of myopathy or neuropathy [21]. For example, Bozkurt et al reported a 97% classification performance using fifteenth order AR models, Yule–Walker, Burg, covariance, modified covariance, and subspace-based methods to extract features from 1200 sEMG, applying high-resolution and a high-sampling rate invasive electrodes implanted in a bicep brachii muscle [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors use autoregressive models and the characteristics of random processes, such as first and second moments and others, in tasks related with classification of myopathy or neuropathy diseases. For example, Bozkurt et al report 97% in performance using fifteenth order autoregressive models (AR) Yule-Walker, Burg, Covariance, Modified Covariance and subspace base methods to extract features from 1200 sEMG, applying high resolution and high sampling rate in invasive electrodes implanted in a Bicep brachii muscle [16].…”
Section: Introductionmentioning
confidence: 99%